2010
DOI: 10.1002/aur.111
|View full text |Cite
|
Sign up to set email alerts
|

MEG detection of delayed auditory evoked responses in autism spectrum disorders: towards an imaging biomarker for autism

Abstract: Motivated by auditory and speech deficits in autism spectrum disorders (ASD), the frequency dependence of superior temporal gyrus (STG) 50 msec (M50) and 100 msec (M100) neuromagnetic auditory evoked field responses in children with ASD and typically developing controls were evaluated. Whole-cortex magnetoencephalography (MEG) was obtained from 17 typically developing children and 25 children with ASD. Subjects were presented tones with frequencies of 200, 300, 500, and 1,000 Hz, and left and right STG M50 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

37
264
8
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 251 publications
(315 citation statements)
references
References 45 publications
37
264
8
1
Order By: Relevance
“…The SH-V interpeak latency of the auditory brainstem response was longer in ASD patients than in control patients (6). Event-related potentials and magnetoencephalography studies also showed delayed responses to auditory stimuli in ASD (6,7,8). Although these electrophysiological studies showed auditory processing differences between autistic and control patients, the cause of auditory hypersensitivity remains unknown.…”
Section: Introductionmentioning
confidence: 93%
“…The SH-V interpeak latency of the auditory brainstem response was longer in ASD patients than in control patients (6). Event-related potentials and magnetoencephalography studies also showed delayed responses to auditory stimuli in ASD (6,7,8). Although these electrophysiological studies showed auditory processing differences between autistic and control patients, the cause of auditory hypersensitivity remains unknown.…”
Section: Introductionmentioning
confidence: 93%
“…These neuroimaging techniques provide a way to assess cortical networks during perception of a stimulus, such as sound in a background of noise, [24] and the results give a more fine-tuned localization when used in combination. Because their excellent temporal resolution, they are used for connectivity analysis in auditory processing [25,26] . Compared with EEG, MEG produces less distortion.…”
Section: Imaging Techniques Availablementioning
confidence: 99%
“…Four reasons that have been suggested as to why this neuroimaging technique is useful include the following: it can provide evidence of the mechanisms of cortical neural activity that occur in central APD (CAPD) and what kind of compensation occurs; it enables visualization of the link between patient performance and neural structures in clinical testing; if neural pathologies are identified, there can be new, better management of the condition based on the indicated neural abnormalities; and it can be used to determine how much restoration of normal neural activity in CAPD occurs via interventional management of CAPD patients [25] . MEG in combination with ABR can track neural activity at the start of a neural signal from the structures just below the midbrain up to the higher auditory cortex [26] . MEG and EEG can assess selective attention because it has been shown that attention causes a significant change in the M100 and N100 potentials, respectively, in normal listeners when attending to a particular signal when two signals are presented at the same time [17] .…”
Section: Imaging Techniques Availablementioning
confidence: 99%
See 2 more Smart Citations